PELUANG OTONOMI DAERAH DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DAERAH PERBATASAN - Ahmad Yasir (Cross-border, 2019)
This article examines regional autonomy: opportunities to reduce backwardness in regions and reduce conflicts in border areas. Intended to improve people's welfare and bring services closer to the community in a short, cheap and satisfying manner. The reality shows that there are still many things that cannot be realized and even increase inequality, frequent conflicts between regions, border problems, ethnic conflicts, and so on. The substance of regional autonomy is that it must be able to be independent in financing development, regulations to regulate the life order of its people without expecting excessive central government intervention. Local governments have their own creations to maximize potential while still balancing the preservation of the surrounding environment. So local independence can be built in synergy between humans and the environment as His creation. The interconnection between humans and humans and their environment is called order, if the order is well developed, there will be no disintegration and conflict that has often occurred after regional autonomy since the beginning of reform. The responsibility of the state and local government becomes the main thing, because the problem of building democracy tends to deviate from the substance of democracy itself.